Microfluidic cell sorter for use in developing red fluorescent proteins with improved photostability - Davis, Lloyd M. (2013)
This paper presents a novel microfluidic cytometer for mammalian cells that rapidly measures the irreversible photobleaching of red fluorescent proteins expressed within each cell and achieves high purity (>99%) selection of individual cells based on these measurements. The selection is achieved by using sub-millisecond timed control of a piezo-tilt mirror to steer a focused 1064-nm laser spot for optical gradient force switching following analysis of the fluorescence signals from passage of the cell through a series of 532-nm laser beams. In transit through each beam, the fluorescent proteins within the cell undergo conversion to dark states, but the microfluidic chip enables the cell to pass sufficiently slowly that recovery from reversible dark states occurs between beams, thereby enabling irreversible photobleaching to be quantified separately from the reversible dark-state conversion. The microfluidic platform achieves sorting of samples down to sub-millilitre volumes with minimal loss, wherein collected cells remain alive and can subsequently proliferate. The instrument provides a unique first tool for rapid selection of individual mammalian cells on the merits of photostability and is likely to form the basis of subsequent lab-on-a-chip platforms that combine photobleaching with other spectroscopic measurements for on-going research to develop advanced red fluorescent proteins by screening of genetic libraries.